Ammonia (NH3) Gas Control System in Chicken Coops Using Fuzzy Logic Based Internet of Things (IoT) Method - Supriadi, Khasbianta; Hartono, Ambran Hartono; Putri, Salsabila Tahta Hirani; Fakhrurraja, Hanif (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2023)
Chicken productivity increases every year, resulting in air pollution in the form of NH3 generated by chicken waste, which is felt by the residents living around the chicken coop. The purpose of this research is to design an ammonia gas control system using Matlab, with the ammonia gas sensor MQ-135 and the humidity sensor DHT11 as parameters, to minimize the ammonia gas levels. This system operates by transmitting information about the condition of ammonia gas levels using a fuzzy logic control system as the technical decision-making mechanism for driving the exhaust fan based on data from the DHT11 and MQ-135 sensors. In this research, the fuzzy logic method was employed to determine the membership functions for the DHT11 sensor (dry, moist, wet) and MQ-135 sensor (normal, moderate, high), resulting in decisions of safe, moderate, and dangerous levels. The data is monitored on a platform through the Blynk app and Thingspeak, thus connecting the Internet of Things (IoT) to the internet network using the NodeMCU ESP8266 as the microcontroller. This research yields an ammonia gas control system that effectively manages air quality affected by chicken waste, with sensor accuracy levels exceeding 97%.